Energy Fluxes and Radiation Effects (EFRE-2020 online) proceedings of 7th International Congress, September 14-26, 2020, Tomsk, Russia - Ratakhin N. A. Nikolay Aleksandrovich (New York, IEEE, 2020)
Title screen